On the design of energy storage systems to achieve wind dispatchability - Wee, Kok Woei (2015)
With increasing penetration level of wind power into grid systems, wind farm operators will eventually be required to commit firm power dispatch similar to most conventional power stations. For the scale of a wind farm, the design of a battery-supercapacitor energy storage system is proposed. The design exploits the technical merits of the two energy storage mediums, in terms of the differences in their specific power and energy densities, and their ability to accommodate different rates of change in the charging/discharging powers.With a developed computational procedure and a proposed coordinated power flows control strategy for the battery and supercapacitor, a least-cost/year hybrid energy storage system design is attained to realize wind power dispatch at a specified confidence level. For the case of large-scale wind generation, a pumped-hydroelectric storage (PHS) scheme is considered. Using a newly designed dispatch strategy, the PHS is able to fully utilize its store energy capacity in each of the pumping and generating operations. Consequently, the PHS life span is not reduced. Through the maximization of the expected economic gain obtainable by incorporating the PHS, the optimal PHS capacities are thereby established.